Social anxiety and vulnerability for problematic drinking in college students: the moderating role of post-event processing*. Issue 5 (2nd September 2016) - Potter, Carrie M.; Galbraith, Todd; Jensen, Dane; Morrison, Amanda S.; Heimberg, Richard G.
Abstract: Socially anxious college students are at increased risk for engaging in problematic drinking (i.e. heavy or risky drinking) behaviors that are associated with the development of an alcohol use disorder. The present study examined whether post-event processing (PEP), repeatedly thinking about and evaluating one's performance in a past social situation, strengthens the association between social anxiety and vulnerability to problematic drinking among college students. Eighty-three college drinkers with high or low social anxiety participated in a social interaction task and were exposed to a manipulation that either promoted or inhibited PEP about the social interaction. Among participants randomized to the PEP promotion condition, those with high social anxiety exhibited a greater urge to use alcohol after the social interaction and greater motivation to drink to cope with depressive symptoms over the week following the manipulation than did those with low social anxiety. These findings suggest that targeting PEP in college drinking intervention programs may improve the efficacy of such programs for socially anxious students.